Practical commentary on therapeutic guidelines for isolated nail lichen planus 2020 - Andrzej K. Jaworek; Przemysław Hałubiec; Judyta Maciejowska-Podosek; Anna Wojas-Pelc (Termedia Publishing House, 2021)
Lichen planus (LP) is a chronic, inflammatory dermatosis characterized by presence of polygonal, flat-raised, purple-red papules and intense itching [1]. Incidence of the disease is estimated at 0.1-1.0%. Apart from the skin, the disease may also affect mucosa, hair and nails (~10% of LP cases). More than 20 clinical and morphological variants of LP have been identified, closely related to location of lesions. Location of lesions is an important diagnostic clue - the most commonly there are symmetrical lesions on wrists, forearms or ankles. The Koebner's symptom and the presence of Wickham striae on the lesion surface are helpful in clinical diagnostics. Dermoscopic criteria (Wickham striae, matt red background, peripheral arrangement of blood vessels) are increasingly common. In ambiguous cases, a biopsy of lesions with subsequent histopathological assessment is recommended. Etiology of LP has not been clearly established yet. Among numerous hypotheses, the most common assumption is that an undefined factor induces an autoimmune response of CD8+ and CD45Ro+ T cells directed to basal epidermal keratinocytes, leading to their apoptosis [1, 2].